Doing the City from the Margins: Critical Perspectives on Urban Marginality. Issue 1 (2nd January 2019) - Aceska, Ana; Heer, Barbara; Kaiser-Grolimund, Andrea
ABSTRACT: This special issue focuses on urban marginality in diverse contexts across the world (Africa, Latin America, Arab States and Europe) and proposes anthropological perspectives on contemporary urbanity that take into account the complexity of the social positions of those city dwellers that are on the margins. Three aspects of urban margins come to the fore. First, urbanites respond to increasing marginalisation through the production of alternative meanings and narratives about the city. While grand, powerful narratives may present cities as 'divided', 'dual' or 'conflicted', urban dwellers may carve out symbolic space through discourses of the non-spectacular and non-political, emerging out of lived space. Second, the cuts and frictions constituting urban margins do not only limit urban dwellers capacities, but can also provide spaces of agentic possibilities. As it is well known, the absence of state control can be turned by versatile urbanites into opportunities of the 'informal' economy. Third, urban dwellers engage in manifold practices that connect and entangle their marginalised position with spaces of power and resources. Through their practices urban margins become a relation to, not a disconnection from the 'centre'. In this special issue we understand 'urban margins' not as essence or entities, but as forms of relations between urban dwellers shaped by processes of political, economic, spatial and social marginalisation. Seen in this way, urban margins constitute a perspective on the urban: a lens to entice comparisons of urban agency in the world of cities [Robinson, J. 2011. "Cities in a World of Cities: The Comparative Gesture." International Journal of Urban and Regional Research 35 (1): 1–23. doi:10.1111/j.1468-2427.2010.00982.x ]].